Cohort study evaluating management of burns in the community in clinical practice in the UK: costs and outcomes. Issue 4 (8th April 2020) - Guest, Julian F; Fuller, Graham W; Edwards, Jacky
Abstract : Objective: To evaluate health outcomes, resource use and corresponding costs attributable to managing burns in clinical practice, from initial presentation, among a cohort of adults in the UK. Design: Retrospective cohort analysis of the records of a randomly selected cohort of 260 patients from The Health Improvement Network (THIN) database who had 294 evaluable burns. Setting: Primary and secondary care sectors in the UK. Primary and secondary outcome measures: Patients' characteristics, wound-related health outcomes, healthcare resource use and total National Health Service (NHS) cost of patient management. Results: Diagnosis was incomplete in 63% of patients' records as the location, depth and size of the burns were missing. Overall, 70% of all the burns healed within 24 months and the time to healing was a mean of 7.8 months per burn. Sixty-six per cent of burns were initially managed in the community and the other 34% were managed at accident and emergency departments. Patients' wounds were subsequently managed predominantly by practice nurses and hospital outpatient clinics. Forty-five per cent of burns had no documented dressings in the patients' records. The mean NHS cost of wound care in clinical practice over 24 months from initial presentation was an estimated £16 924 per burn, ranging from £12 002 to £40 577 for a healed and unhealed wound, respectively. Conclusions: Due to incomplete documentation in the patients' records, it is difficult to say whether the time to healing was excessive or what other confounding factors may have contributed to the delayed healing. This study indicates the need for education of general practice clinicians on the management and care of burn wounds. Furthermore, it is beholden on the burns community to determine how the poor healing rates can be improved. Strategies are required to improve documentation in patients' records, integration of care between different providers, wound healing rates and reducing infection.